Explorando o universo dos números primos - Oliveira, Rafael Américo de [UNESP] (2015)
The aim of this work is a study of prime numbers. We will work with classical subjects of Number Theory, such as, Congruences, The little Fermat's Theorem, the Wilson's Theorem, the Euler's function φ and the Euler's Theorem. Using these results we will investigate primality tests, special prime numbers and functions defining prime numbers